Evaluation of efficacy of chemical, botanicals and beejamrut in growth promotion and management of damping off disease in cauliflower at Udayapur, Nepal - G.C., S.; Khatri, L. (Journal of Agriculture and Forestry University, 2020)
Vegetable contributes 20.74% of the total Agricultural Gross Domestic Products (AGDP) of the country. Among the vegetables produced, cauliflower (Brassica oleracea L. var. botrytis) is one of the important vegetable crops in Nepal. Soil borne pathogens (soil inhabitants and soil transients) are one of the major factors contributing to lower yield in vegetables either through damage of whole crop, or by making them unmarketable. Damping off caused by Pythium, Fusarium, Rhizoctonia, Phytophthora is one of the major disease of vegetables crops. This disease attacks a crop in its two stages i.e. pre-emergence of seeds and in seedling stage. This study was conducted in a sick plot at Ghumne 5 of Belaka Municipality, Udayapur, Nepal with six treatments, each replicated four times. The pathogen causing damping off was identified as Rhizoctonia sp. Among the treatments Beejamrut was found to be superior to other treatments in terms of root length (5.97±0.62cm) and shoot length (13.25±1.16cm). In case of root weight and shoot weight Beejamrut (0.28±0.03g;1.85±0.50g), respectively, gave the similar results to Thiram (0.27±0.01g;1.89±0.4g), respectively. Lowest Percentage Disease Incidence (PDI) was found in Thiram (18.0±1) and Beejamrut (19.0±1) treated plots.